Apartment building, Lot 20, Edinburgh, Castlecrag, [Sydney, New South Wales] - Griffin, Walter Burley, 1876-1937. (1921)
The item includes a plan, front perspective.
Title from acquisition documentation.
Part of the collection: Eric Milton Nicholls collection.
Condition: Good.
Inscription: "LL" monogram [Louise Lightfoot?], "Walter Burley Griffin, Architect"--Lower right.
Also available online
Purchased from Marie and Glynn Nicholls, 2006.
Keywords: Apartments -- New South Wales -- Castlecrag -- Designs and plans -- Photographs; Dwellings -- New South Wales -- Castlecrag -- Designs and plans -- Photographs; Architecture, Domestic -- New South Wales -- Castlecrag -- Designs and plans -- Photographs; Architectural drawing